2007
DOI: 10.1007/s11814-007-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag-sensitized ZnO and its photocatalytic performance under simulated solar light

Abstract: ZnO was prepared rapidly by microwave heating method. The results of scanning electron microscopy show that the leaflike ZnO is composed of self-assembled ZnO particles of 30-50 nm. Ag-sensitized ZnO composite was prepared by UV-photoreduction and glycol reduction, respectively. The composite was characterized by means of scanning electron microscopy, X-ray diffraction and photoluminescence. The ZnO and Ag/ZnO prepared were applied in photocatalytic degradation of phenol and methyl orange as model of organic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…, and Ag can improve the photocatalytic performance of semiconductor ZnO, for these can act as electron trapping agents to restrain electron hole recombination rate [15][16][17][18][19]. Among doped nanostructures, great efforts have been made to explore for potential applications in various fields due to the miscellaneous properties of Ce/ZnO nanostructures [20][21][22][23][24][25][26].…”
Section: +mentioning
confidence: 99%
“…, and Ag can improve the photocatalytic performance of semiconductor ZnO, for these can act as electron trapping agents to restrain electron hole recombination rate [15][16][17][18][19]. Among doped nanostructures, great efforts have been made to explore for potential applications in various fields due to the miscellaneous properties of Ce/ZnO nanostructures [20][21][22][23][24][25][26].…”
Section: +mentioning
confidence: 99%
“…The experimental range was based on published reports [19,20]. After running a total of 20 experiments, including 5 replicates at the center point, a second-order (quadratic) model was used to fit the experimental data that express the functionalization efficiency as a function of independent variables, Eq.…”
Section: Experimental Designmentioning
confidence: 99%
“…In addition, attempts have also been made to design ZnO photocatalysts with effective charge separation and storage of the photoexcited charges. Recently, it has been shown that loading of silver nanoparticles (AgNPs) on ZnO surface can reduce photocorrosion, improve absorption of visible light, and increase the photocatalytic efficiency of ZnO.…”
Section: Introductionmentioning
confidence: 99%